The neoliberal state, recognition and indigenous rights: new paternalism to new imaginings - Bargh, Maria; Howard-Wagner, Deirdre; Altamirano-Jiménez, Isabel (Austrlian National University, 2018)
Keywords: civil Rights; crown law; crown policy; tikanga | indigenous law

Beyond biculturalism: the politics of an indigenous minority - O'Sullivan, Dominic (Huia, 2007)
"Beyond Biculturalism is a critical analysis of contemporary Maori public policy. Bicultural political theory dominated Maori/Crown relationships during the 1980s and 1990s and O'Sullivan argues that biculturalism inevitably makes Maori the junior partner in a colonial relationship that obstructs Maori aspirations to self-determination. The politics of indigeneity and self-determination are discussed as alternative political ideas for thinking about Maori relationships with the state. Against this background, and by drawing on Australian and Canadian comparisons, the book examines contemporary Maori political issues such as the Foreshore and Seabed Act 2004, Maori parliamentary representation, the 'one law for all' ideology, settlements of Maori grievances against the Crown, and Maori economic development."–BOOK JACKET.
Keywords: bicultural; crown policy; ethnic identity; government relations; iwi taketake; kāwanatanga; race relations; rangatiratanga; tāngata whenua

Indigenous Peoples and Demography: The Complex Relation between Identity and Statistics - Chapter 2 Building ethnic boundaries in New Zealand; representations of Maori identity in the census - Kukutai, Tahu (Berghahn Books, 2011)
When researchers want to study indigenous populations they are dependent upon the highly variable way in which states or territories enumerate, categorise and differentiate indigenous people. In this volume, anthropologists, historians, demographers and sociologists have come together for the first time to examine the historical and contemporary construct of indigenous people in a number of fascinating geographical contexts around the world, including Canada, the United States, Colombia, Russia, Scandinavia, the Balkans and Australia. Using historical and demographical evidence, the contributors explore the creation and validity of categories for enumerating indigenous populations, the use and misuse of ethnic markers, micro-demographic investigations, and demographic databases, and thereby show how the situation varies substantially between countries.
Keywords: anthropology; census; crown policy; ethnic identity